2022
DOI: 10.3390/pathogens11060656
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of the Iron-Chelator, DIBI, against Multidrug-Resistant Canine Methicillin-Susceptible Staphylococcus pseudintermedius: A Preliminary Study of Four Clinical Strains

Abstract: Staphylococcus pseudintermedius is an important opportunistic pathogen causing various infections in dogs. Furthermore, it is an emerging zoonotic agent and both multidrug-resistant methicillin-resistant S. pseudintermedius (MRSP) as well as methicillin-susceptible (MSSP) strains represent an important therapeutic challenge to veterinary medicine and pose a potential threat to human health. We tested representative S. pseudintermedius clinical strains from dogs suffering from otitis externa for their susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…Furthermore, the presence of mecA significantly affects the antibiotic resistance of S. pseudintermedius [ 47 ]. Our findings are consistent with those of other studies [ 38 , 48 ]. MRSP isolates exhibited multidrug resistance, all isolates of the MRSPs being resistant to ampicillin; 80% resistant to oxacillin, cefotaxime, and sulfamethoxazole/trimethoprim; 70% resistant to norfloxacin, enrofloxacin, and doxycycline; and 60% resistant to amoxicil-lin–clavulanic acid, ceftriaxone, gentamicin, and erythromycin.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, the presence of mecA significantly affects the antibiotic resistance of S. pseudintermedius [ 47 ]. Our findings are consistent with those of other studies [ 38 , 48 ]. MRSP isolates exhibited multidrug resistance, all isolates of the MRSPs being resistant to ampicillin; 80% resistant to oxacillin, cefotaxime, and sulfamethoxazole/trimethoprim; 70% resistant to norfloxacin, enrofloxacin, and doxycycline; and 60% resistant to amoxicil-lin–clavulanic acid, ceftriaxone, gentamicin, and erythromycin.…”
Section: Discussionsupporting
confidence: 94%
“…DIBI treatment was efficient in reducing bacterial load in both lung homogenate and BALF. In agreement with our findings on DIBI-restricted P. aeruginosa growth, it has previously been demonstrated that iron-withdrawal chelator DIBI has also been shown to disrupt the staphylococcal biofilm growth [18]. In previous studies published by our group we found that in sepsis induced by colon ascendens stent peritonitis (CASP), DIBI treatment significantly decreased the bacterial count in blood and peritoneal lavage fluid [19].…”
Section: Discussionsupporting
confidence: 92%
“…Dogs and cats were sampled between October 2022 and June 2023 in order to isolate Staphylococcus spp. To isolate commensal Staphylococcus , a single swab (Cary–Blair sterile transport swabs, DELTALAB, Barcelona, Spain) was first introduced in the nasal cavity and then in the auricular cavity, approximately 3 cm [ 25 , 26 ], from healthy asymptomatic dogs and cats. Before taking the samples, the veterinarians performed a clinical examination in which they assessed the animals’ vital signs to confirm that they were within normal ranges, thus classifying them as asymptomatic healthy animals.…”
Section: Methodsmentioning
confidence: 99%